ANALISIS SWOT TERHADAP IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH SEBAGAI KAJIAN STRATEGIS DALAM PENGEMBANGAN PENGELOLAAN PENDIDIKAN DI SD NO. 6 DARMASABA - Ida Bagus Gede Surya Abadi; Ni Ketut Adi Widaswari; Ni Luh Mia Sri Diana Puspita Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Improving the quality of basic education highly depends on the effectiveness of School-Based Management (SBM) implementation, which requires autonomy, participation, and accountability. This study aims to analyze the implementation of SBM, identify strengths, weaknesses, opportunities, and threats, and formulate management strategies at SD No. 6 Darmasaba. A descriptive qualitative method was employed through field observations, interviews, and documentation, supported by SWOT analysis to map the school’s conditions. The results show that SBM implementation is generally running well with a score of 81.30, achieving excellence in infrastructure, finance, curriculum management, and service quality. However, significant imbalances were found, particularly weaknesses in public relations management, learning innovation, and counseling services. Based on the SWOT analysis, the school has great potential to utilize policy support and technology but faces threats from competition and quality demands. This study proposes four main strategies recommending strengthened partnerships, optimized technology use, and enhanced innovation to make school management more balanced, effective, and competitive.